Encountering Nature, Experiencing Courtly Love, and Romance of the Rose: Generic Standpoints, Interpretive Practices, and Human Interchange in 12th-13th Century French Poetics - Prus, Robert (Qualitative Sociology Review, 2014)
Whereas the fields of poetic expression and pragmatist philosophy may seem some distance apart, a closer examination of the poetics literature from the early Greeks onward provides testimony to the more general viability of the pragmatist analysis of community life, particularly as this has come to be associated with pragmatism’s sociological derivative, symbolic interaction. Following a brief overview of the Greek, Roman, and Christian roots of contemporary fictional representations, attention is given to the ways that pragmatist concerns with human activity were addressed within the context of poetic expression in 12th-13th century France. Whereas the pre-Renaissance texts considered here exhibit pronounced attentiveness to Christian theology, they also build heavily on Latin sources (especially Virgil and Ovid [see Prus 2013a]). Among the early French poets who address the matters of human knowing and acting in more direct and consequential terms are: Alan de Lille (c. 1120-1203) who wrote The Plaint of Nature and Anticlaudianus; Andreas Capellanus (text, c. 1185) the author of The Art of Courtly Love; and Guillaume de Lorris (c. 1212-1237) and Jean de Meun (c. 1235-1305) who, in sequence, co-authored The Romance of the Rose. Given our interest in the ways in which those in the poetic community helped sustain an analytic focus on human lived experience, particular consideration is given to these early French authors’ attentiveness to (1) the relationships, identities, activities, and tactical engagements that people develop around romantic relationships; (2) the sense-making activities of those about whom they write, as well as their own interpretive practices as authors and analysts; (3) the ways in which the people within the communities that they portray knowingly grapple with religious and secular morality (and deviance); and (4) more generic features of human standpoints and relationships. Clearly, the poets referenced here are not the first to pursue matters of these sorts. However, their materials are important not only for their popular intrigues, creativity, and effectiveness in “moving poetics out of the dark ages” but also for encouraging a broader interest in considerations of the human condition than that defined by philosophy and rhetoric.